2013
DOI: 10.1080/1369118x.2012.656137
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Online Information Seeking

Abstract: This paper reports on a study designed to explore individual differences in uncertainty-reducing behavior regarding new and existing friends via online information seeking (OIS). Personality traits and social context were measured by surveying a sample of 377 Facebook users. Global uncertainty had a positive relationship with active information seeking about new friends, whereas communication apprehension was associated with seeking information about existing friends. The geographic proximity of close friends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Kim and Stanton (2015) in a multilevel analysis discuss about institutional and individual factors affecting scientists' data-sharing behaviours. Stefanone et al (2013) studied the antecedents of online information seeking and found individual differences as strong motives for uncertainty or assurance in the same. They also ascertain that personality affects users' online behaviour as in the offline world.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Kim and Stanton (2015) in a multilevel analysis discuss about institutional and individual factors affecting scientists' data-sharing behaviours. Stefanone et al (2013) studied the antecedents of online information seeking and found individual differences as strong motives for uncertainty or assurance in the same. They also ascertain that personality affects users' online behaviour as in the offline world.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Previous studies have found that demographic variables, such as gender and age, show significant impact on the composition of media repertoires (e.g., Yuan, 2011). In addition, users with different psychological characteristics may prefer different information-seeking approaches (Stefanone, Hurley, & Yang, 2013). Future studies need to further control these variables and examine the interaction effects between the self-reported and objective measures employed to build information repertoires.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Although Information,Communication & Society 377 initial interactions between strangers may be awkward and include inquiries about the weather or one's career, today we have the option of reducing these initial uncertainties by gathering information about potential conversation partners online. In the tradition of uncertainty reduction theory (Berger & Calabrese, 1975), research shows that individuals use the Internet to gather information about new and existing relationships for exactly this purpose (Stefanone, Hurley, & Yang, 2013). The consequences of information asymmetries are numerous in the economic and sociological literature.…”
Section: Introductionmentioning
confidence: 99%